HDAC inhibitor SAHA enhances antitumor immunity via the HDAC1/JAK1/FGL1 axis in lung adenocarcinoma - Tao Yu; Yuan Fang; Yongqian Shu; Tong Hu; Tingting Xu; Duo Xu; Yunru Gu; Yang-Yue Xu; Hao-Yang Shen; Pei Ma (Journal for ImmunoTherapy of Cancer, 2024)
Background Histone deacetylase (HDAC), a kind of protease that regulates gene expression by modifying protein acetylation levels, is usually aberrantly activated in tumors. The approved pan-HDAC inhibitors (HDACi) have exhibited clinical benefits for hematopoietic malignancies. Recently, HDACis have emerged as enhancers of antitumor immunity. However, the effect of HDACs on the tumor immune microenvironment of lung adenocarcinoma (LUAD) and the underlying mechanism is largely unknown.Methods C57BL/6J and BALB/c nude mice with subcutaneous tumors were used for in vivo therapeutic effects and mechanistic investigations. Flow cytometry was used to measure the toxicity and exhaustion of human CD8+T cells after co-culturing with tumor cells and to determine the immunophenotype of tumor-infiltrating CD8+T cells. A series of experimental techniques, including RNA sequencing, quantitative PCR, western blot, ELISA, mass spectrometry, co-immunoprecipitation, chromatin immunoprecipitation and immunohistochemistry, were used to explore the underlying molecular mechanism.Results The pan-HDACi vorinostat (SAHA) promoted CD8+T cell infiltration and effector function in LUAD through suppressing FGL1, a newly identified major ligand of LAG-3. Mechanistically, SAHA inhibited the activity of HDAC1, an essential deacetylase of JAK1. This increased the acetylation level of JAK1 at lysine 1109, thus promoting its proteasomal degradation and subsequently reducing STAT3-driven FGL1 transcription. The combination regimen of SAHA and anti-LAG-3 therapy was further explored in an immunocompetent LUAD mouse model. Compared with those receiving control or single agent treatments, mice receiving combination therapy exhibited a lower tumor burden and superior CD8+T-cell-killing activity.Conclusions Our results revealed a novel mechanism by which the HDACi SAHA potentiates CD8+T-cell-mediated antitumor activity through the HDAC1/JAK1/FGL1 axis, providing a rationale for the combined use of HDACis and immunotherapy.